SELECTIVE ISOLATION OF Dactylosporangium AND Micromonospora FROM THE SOIL OF KARST CAVE OF SIMEULUE ISLAND AND THEIR ANTIBACTERIAL POTENCY - Ade Lia Putri; I Nyoman Sumerta (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Karst is a unique ecosystem that consists of a thin soil layer on the carbonate rocks. It has a diverse microorganism, especially actinomycetes group, which might potentially produce beneficial secondary metabolites that remain unknown. In this study, we were interested in isolating Dactylosporangium and Micromonospora that have been potentially reported as antibiotic sources. We used two methods using the chemical germicide (pretreatment 1.5% phenol) compared with the SDS-YE (0.05% SDS pretreatment). Thirty-nine isolates actinomycetes were successfully isolated from two samples of the karst cave soils. Thirteen isolates were obtained by using the germicide chemical method and closely related to the genera of Dactylosporangium and Micromonospora. On the other hand, the SDS-YE grew twenty-six isolates which closely related to 11 genera of actinomycetes (Catenulispora, Nocardia, Rhodococcus, Ornithinimicrobium, Catellatospora, Dactylosporangium, Micromonospora, Streptacidiphilus, Streptomyces, Nonomuraea, and Streptosporangium). These results suggest that 1.5% of phenol pretreatment could preserve the genera of Dactylosporangium and Micromonospora, while the Streptomyces and other rare actinomycetes were killed. Among all isolates, only 7 showed the antibacterial activity on tested bacteria. Even though the antibacterial activity of those isolates was not high, the isolation of actinomycetes from a specific substrate is necessary to be conducted on exploring the richness of our natural resources.